Women's preferences, impacts, and satisfaction with companion support during labour and delivery experiences in Oman - Nasar Alwahaibi; Fatema Alajaimi; Hoor Alhabsi; Alzahra Alkalbani; Rodina Aljulandani (Frontiers in Global Women's Health)
BackgroundThis is the first study to combine both the women's preferences, impacts, and satisfaction during their labour and delivery experience and their companions for their role and impacts. Previously published papers examined either the preferences of pregnant women or those of their companions, which are few. Women's preferences, impacts, and satisfaction with their companions during labour and delivery were evaluated in this study.MethodsThis cross-sectional observational study was conducted between June 2022 and April 2024. As part of this study, labouring women as well as their companions were interviewed separately face-to-face in a private place, and all answers were kept anonymous and confidential. We evaluated each category separately based on two separate sections.ResultsThis study included a total of 444 labouring women and an equal number of companions, with mean ages of 32.25 years and 42.66 years, respectively. The majority of women and companions were housewives with college degrees. Among companions, mothers and husbands were the most preferred, and they were typically present from admission to discharge. Among women who had companions, 84.1% reported feeling calmer and more comfortable. 91.9% of companions supported women with encouraging words, and 92.6% perceived their support as highly beneficial to the women. Women expressed 94.8% satisfaction with the medical staff and 87.6% satisfaction with hospital services, while companions reported 96.6% and 74.8% satisfaction with the medical staff and hospital services, respectively.ConclusionsLabouring women appreciated and valued the presence of companions during childbirth as they had positive impacts. Mothers are the most preferred companions and preferred to be present from admission until discharge. Most companions support their labouring women by encouraging wards. Labouring women and companions were satisfied with the medical team and services provided to them. The presence and role of companions during the childbirth process are crucial and warrant emphasis.